As contribuições dos multiletramentos e da multimodalidade no ensino da leitura e escrita em língua portuguesa: um olhar para a retextualização no nono ano do ensino fundamental na educação básica - Fiorini, Maria Célia (2022)
This research develops social practices of reading and writing in multimodal genres in the daily life of Portuguese language classes in the ninth grade of elementary school with a view to the retextualization of chronicles. Under the contributions of Bakhtin (2003, 2006), Rojo (2012), Ribeiro (2020, 2021), Coscarelli and Cani (2016), CostaHübes (2014), Street (2014), Geraldi (2006, 2019) and Antunes (2003) discussed the training of young people open to new knowledge of social practices of reading and writing. We used participatory research as a methodology, which had the participation of students in the ninth year of elementary school at a state public school in the North of the Espírito Santo State. For that, we developed the research in the classroom, from the perspective of reading and writing in multiliteracies, with the chronic textual genre. In view of the development of the retextualizations carried out, we can say that this type of activity was of paramount importance for perspectives of successful practices in the classroom.